-1 over 3q-7=-3

## how do you do two step equations

Tutors, please sign in to answer this question.

# 3 Answers

**1**

**- ---- q - 7 = - 3**

**3**

. + 7 + 7

**1**

**- ---- q = 4**

**3**

3 3

×(- —) ×( - —)

1 1

**q = - 12**Hi Alexis;

-1 over 3q-7=-3

This is...

-1/(3q-7)=-3

First, let's eliminate the complicated fractions.

We will multiply both sides by (3q-7)...

(3q-7)[-1/(3q-7)]=-3(3q-7)

Let's cancel where appropriate...

(3q-7)[-1/(3q-7)]=-3(3q-7)

-1=-3(3q-7)

Let's divide both sides by -3...

-1/-3=[-3(3q-7)]/-3

1/3=3q-7

Let's add 7 to both sides...

7+1/3=3q-7+7

7 1/3=3q

Because 7 1/3=22/3...

22/3=3q

Let's multiply both sides by 1/3 to achieve the isolation of q...

(22/3)(1/3)=3q(1/3)

22/9=q

Let's check our work...

The original equation was...

-1/(3q-7)=-3

-1/[3(22/9)-7]=-3

-1/[(22/3)-7]=-3

Because 7=21/3

-1/[(22/3)-(21/3)]=-3

-1/(1/3)=-3

Because dividing by 1/3 is equal to multiplying by 3...

-1(3)=-3

-3=-3

First - multiply both sides of the equation by the bottom portion of the fraction (3q-7) to eliminate the fraction.

Next - you are left with -1=-9q+21

Then - treat it like a normal equation. Subtract 21 from both sides to get -22=-9q

Finally - divide both sides by -9, and you find that q = 22/9. (or "22 over 9")

Good luck!

## Comments

(-1 over3)q-7=-3 or (-1/3)q - 7 = -3

Comment